Isolation and Identification of Phenol Degrading Bacteria in Refuse Dumping Site - Muhammad, Muhammad Bashir; Aisami, Abubakar; Dauda, Maianguwa Abdulrashid; Adeseye, Abdullahi Sa’adu; Umaru, Isaac John; Oluwabunmi, Helen; Habibu, Bilyaminu; Oladele, Gloria Omonefe (Darul Yasin Al Sys, 2024)
Phenol is a harmful compound found in soil, and its removal is crucial for human health. Phenol or hydroxybenzene, is both a synthetically and naturally produced aromatic compound. Microorganisms capable of degrading phenol are common and include both aerobes and anaerobes. In this study, researchers collected soil samples from INEX refuse dumping site along Bajoga road of kwami, Gombe state, and determined the abundance of heterotrophic and degradation bacteria using serial dilution and most probable number (MPN) methods. This experimental research study was carried out in order to isolate and identify phenol-degrading bacteria in polluted soil, the effect of concentration and pH was analysed during the procedure. Bacteria was isolated from contaminated soil and sub-cultured in a Mineral-salt media which was prepared with phenol added as the only carbon source needed for the bacterial growth, The bacterial isolate was identified as Escherichia coli a gram-negative bacteria. The favourable concentration and pH required for the growth of the bacteria was determined as 200mg/L and pH 7 respectively. These findings have significance in bioremediation for employing suitable bacteria in suitable condition for solving environmental pollution crises.